PENGGUNAAN MEDIA VISUAL TIGA DIMENSI UNTUK MENINGKATKAN HASIL BELAJAR BANGUN RUANG PADA KELAS V SD NEGERI 006 RAMBAH - Septriyani Gebi (Dharmas Education Journal (DE_Journal), 2021)
The purpose of this study is to describe the use of three-dimensional visual media in improving learning outcomes in spatial form. This type of research applies the Classroom Action Research (CAR) method. This research was conducted in two meetings. The completeness of this researcher is in the form of a written test that is multiple choice. The subject of the study was the fifth grade teacher of SD Negeri 006 Rambah, which consisted of 14 students, 6 male students and 8 female students. The results of this study indicate that student learning outcomes in the material of spatial construction are increased through the use of three-dimensional visual media. The average value of student learning outcomes at the first meeting was 53%, while the second meeting was 81.14%. The percentage of the sum of the two meetings was 28.14%. This states that the use of three-dimensional visual media in spatial learning can improve student learning outcomes in class V SD Negeri 006 Rambah.